Cation‐Anchoring‐Induced Efficient n‐Type Thermo‐Electric Ionogel with Ultra‐High Thermopower - Wenchao Zhen; Chengshuai Lu; Duo Li; Guangfan Meng; Hongqin Wang; Yifei Jiang; Jiang Lou; Wenjia Han (Advanced Science)
Abstract Ionogels have emerged as promising candidates for low‐grade thermal energy harvesting due to their leak‐free electrolytes, exceptional flexibility, thermal stability, and high thermopower. While substantial progress in the thermoelectric performance of p‐type ionogels, research on n‐type ionic materials lags behind. Striking a harmonious balance between high mechanical performance and thermoelectric properties remains a formidable challenge. This work presents an advanced n‐type ionogel system integrating polyethylene glycol diacrylate (PEGDA), hydroxyethyl methacrylate (HEMA), 1‐allyl‐3‐methylimidazolium chloride ([AMIM]Cl), and bacterial cellulose (BC) through a rational design strategy. The synergistic combination of photo‐polymerization and hydrogen‐bonding networks effectively immobilizes imidazolium cations while enabling rapid chloride ion transport, creating a pronounced cation‐anion mobility disparity that yields a substantial negative ionic Seebeck coefficient of −7.16 mV K⁻¹. Furthermore, BC's abundant hydroxyl groups establish multivalent hydrogen bonds within the ternary polymer matrix, endowing the composite with exceptional mechanical properties—notably a tensile strength of 3.2 MPa and toughness of 4.1 MJ m⁻3. Moreover, the ionogel exhibits sensitive responses to stimuli such as pressure, strain, and temperature. The thermoelectric modules fabricated can harness body heat to illuminate a bulb, showcasing great potential for low‐grade energy harvesting and ultra‐sensitive sensing.